Strategi Kehumasan Dalam Pelayanan Informasi Publik Di Pusat Pelatihan Dan Pengembangan Dan Kajian Manajemen Pemerintahan Lembaga Administrasi Negara - Sri Kartika; Abdi Abdi; Nasrulhaq Nasrulhaq (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
The study aimed to discover the public relations strategy in public information services at the Center for Training and Development and Government Management Studies at the State Administration Agency (Puslatbang KMP LAN). Data were obtained through data collection techniques using observation, interviews, and documentation studies which were carried out with data analysis techniques consisting of data reduction, data presentation, and conclusions. The results showed that aspects of 1) problem definition, namely the information media managed by public relations was not yet fully known by stakeholders, so that information was not conveyed thoroughly; 2) planning and programming, namely public relations coordinating with teaching facilitators to socialise the social media and connecting every social media; 3) action and communication, namely public relations conducting two-way communication to stakeholders, public relations using electronic and non-electronic media in inserting social media so that stakeholders know the information funnel and public relations utilising several of social media in disseminating information; 4) evaluation, namely that all social media had been known to stakeholders and could be accessed so that comprehensive and up-to-date information was achieved.